Novel compound heterozygous NMNAT1 variants associated with Leber congenital amaurosis - Siemiatkowska, Anna; van den Born, L. Ingeborgh; van Genderen, Maria M.; Bertelsen, Mette; Zobor, Ditta; Rohrschneider, Klaus; van Huet, Ramon A.C.; Nurohmah, Siska; Klevering, B. Jeroen; Kohl, Susanne; Faradz, Sultana M.H.; Rosenberg, Thomas; et al. (Molecular vision, 2014)
Purpose - The gene encoding nicotinamide nucleotide adenylyltransferase 1 (NMNAT1) was recently found to be mutated in a subset of patients with Leber congenital amaurosis (LCA) with macular atrophy. The aim of this study was to determine the occurrence and frequency of NMNAT1 mutations and associated phenotypes in different types of inherited retinal dystrophies. - - Methods - DNA samples of 161 patients with LCA without genetic diagnosis were analyzed for variants in NMNAT1 using Sanger sequencing. Variants in exon 5 of NMNAT1, which harbors the majority of the previously identified mutations, were screened in 532 additional patients with retinal dystrophies. This cohort encompassed 108 persons with isolated or autosomal recessive cone-rod dystrophy (CRD), 271 with isolated or autosomal recessive retinitis pigmentosa (RP), and 49 with autosomal dominant RP, as well as 104 persons with LCA in whom the causative mutation was previously identified. - - Results - Compound heterozygous alterations were found in six patients with LCA and in one person with early-onset RP. All except one carried the common p.E257K variant on one allele. Macular atrophy was absent in one patient, who carried this variant in combination with a truncating mutation on the other allele. The p.E257K alteration was also found in a heterozygous state in five individuals with LCA and one with RP while no mutation was detected on the other allele. Two individuals with LCA carried other NMNAT1 variants in a heterozygous state, whereas no NMNAT1 variants in exon 5 were identified in individuals with CRD. The p.E257K variant was found to be enriched in a heterozygous state in individuals with LCA (0.94%) compared to Caucasian controls (0.18%), although the difference was statistically insignificant (p=0.12). - - Conclusions - Although macular atrophy can occur in LCA and CRD, no NMNAT1 mutations were found in the latter cohort. NMNAT1 variants were also not found in a large group of patients with sporadic or autosomal recessive RP. The enrichment of p.E257K in a heterozygous state in patients with LCA versus controls suggests that this allele could act as a modifier in other genetic subtypes of LCA.
Gesehen am 12.08.2020